(untitled) (Revista Contexto & Saúde, 2026)
Specialized Dental Centers (CEO) provide secondary oral health care and have monthly production targets to meet. Objective: To analyze the achievement of production targets by CEO in the state of Santa Catarina in 2018. This is a quantitative cross-sectional study using secondary data collected from the Outpatient Information System of the Department of Informatics of the Unified Health System (DATASUS). Forty-seven Specialized Dental Centers in Santa Catarina were analyzed, comprising 27 type I CEO, 17 type II CEO, and 3 type III CEO. The achievement of goals was evaluated according to the 4 established goals by specialty: basic, periodontal, endodontic, and surgical procedures, and according to the health macro-region, as per Attachment XL of Consolidation Ordinance of Ministry of Health n. 6/2017. Only 5 CEO met all 4 goals, with periodontics being the specialty that met the most goals in type I CEOs, and basic procedures for type II and III CEOs. The health macro-region with the highest number of goals met was Planalto Norte e Nordeste. Most CEO did not reach the production goals. The worst performance occurred in the Meio Oeste and Serra Catarinense health macro-region, and the best performance in the Planalto Norte e Nordeste health macro-region.